Growth effects of consumption jealousy in a two-sector model - Georg Duernecker (Institute for Advanced Studies (IHS), 2007)
This paper aims at analyzing the implications of individuals' consumption jealousy on the dynamic structure of a two-sector model economy. We find that status-seeking substantially influences both, the long-term properties and the adjustment behavior of the model. Depending on the status motive, productivity disturbances might induce countercyclical responses of work effort whereas preference shocks are expected to generate an overshooting relative capital intensity. Generally we find that, for empirically plausible values of the intertemporal elasticity of substitution, a higher degree of consumption jealousy induces agents to devote more time to education which stimulates human capital accumulation and hence promotes economic growth.
Keywords: D91; E21; O41; 330; status-seeking; economic growth; transitional dynamics; human capital; Wirtschaftswachstum; Konsumentenverhalten; Neid; Humankapital; Wachstumstheorie; Mehr-Sektoren-Modell